El dia que el perro dijo, "quiquiriqui" - McPhail, David, 1940- (New York : Scholastic Inc., 1999)
The farm animals are bored until a big wind strikes the barnyard.
Accelerated Reader AR
Keywords: Domestic animals -- Juvenile fiction; Animal sounds -- Juvenile fiction; Winds -- Juvenile fiction; Spanish language materials -- Juvenile fiction